Molecular and pharmacological aspects of piperine as a potential molecule for disease prevention and management: evidence from clinical trials - Tripathi A.K.; Ray A.K.; Mishra S.K. (My University, 2025)
Background: Piperine is a type of amide alkaloid that exhibits pleiotropic properties like antioxidant, anticancer, anti-inflammatory, antihypertensive, hepatoprotective, neuroprotective and enhancing bioavailability and fertility-related activities. Piperine has the ability to alter gastrointestinal disorders, drug-metabolizing enzymes, and bioavailability of several drugs. The present review explores the available clinical and preclinical data, nanoformulations, extraction process, structure–activity relationships, molecular docking, bioavailability enhancement of phytochemicals and drugs, and brain penetration properties of piperine in the prevention, management, and treatment of various diseases and disorders. Main body: Piperine provides therapeutic benefits in patients suffering from diabetes, obesity, arthritis, oral cancer, breast cancer, multiple myeloma, metabolic syndrome, hypertension, Parkinson's disease, Alzheimer’s disease, cerebral stroke, cardiovascular diseases, kidney diseases, inflammatory diseases, and rhinopharyngitis. The molecular basis for the pleiotropic activities of piperine is based on its ability to regulate multiple signaling molecules such as cell cycle proteins, anti-apoptotic proteins, P-glycoprotein, cytochrome P450 3A4, multidrug resistance protein 1, breast cancer resistance protein, transient receptor potential vanilloid 1 proinflammatory cytokine, nuclear factor-κB, c-Fos, cAMP response element-binding protein, activation transcription factor-2, peroxisome proliferator-activated receptor-gamma, Human G-quadruplex DNA, Cyclooxygenase-2, Nitric oxide synthases-2, MicroRNA, and coronaviruses. Piperine also regulates multiple signaling pathways such as Akt/mTOR/MMP-9, 5′-AMP-activated protein kinase-activated NLR family pyrin domain containing-3 inflammasome, voltage-gated K+ current, PKCα/ERK1/2, NF-κB/AP-1/MMP-9, Wnt/β-catenin, JNK/P38 MAPK, and gut microbiota. Short conclusion: Based on the current evidence, piperine can be the potential molecule for treatment of disease, and its significance of this molecule in the clinic is discussed. Graphical abstract: [Figure not available: see fulltext.] © 2022, The Author(s).